1972
DOI: 10.1111/j.1467-8306.1972.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Channel Stability on the Lower Ohio River∗

Abstract: The meander loop pattern of the lower Ohio River has changed very little over the last thousand years. Point bar complexes are deposited and destroyed quite rapidly in comparison. KEY WORDS ; Channel stability, Meanders, Ohio River, Point bars.ADIOCARBON dates of organic matter R from the Black Bottom alluvium indicate that the meander loops of the lower Ohio River between Evansville, Indiana, and Brookport, Illinois, have an unusual degree of stabi1ity.l These dates suggest that the Bottom had reached its pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…This mechanistic interpretation was largely based on modern Midwest climatology, where warm-season precipitation is dominant over winter precipitation (~75% vs ~25%, respectively), and the association between many of the largest modern floods and the occurrence of warm-season atmospheric river events originating from the Gulf of Mexico (Dirmeyer and Kinter, 2010; Lavers and Villarini, 2013). Other work from the Midwest, including along the Ohio River (Alexander and Nunnally, 1972; Counts et al, 2015; Stafford, 2004) and White River in Indiana (Herrmann and Monaghan, 2018) also shows variability in floodplain construction and the accumulation of floodplain alluvium that further suggests a connection between Holocene fluvial dynamics and climatic variability. Although climate is accepted as a likely driver of floodplain construction, the nature and timing of floodplain construction on large Midwest streams like the Ohio River is not resolved.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This mechanistic interpretation was largely based on modern Midwest climatology, where warm-season precipitation is dominant over winter precipitation (~75% vs ~25%, respectively), and the association between many of the largest modern floods and the occurrence of warm-season atmospheric river events originating from the Gulf of Mexico (Dirmeyer and Kinter, 2010; Lavers and Villarini, 2013). Other work from the Midwest, including along the Ohio River (Alexander and Nunnally, 1972; Counts et al, 2015; Stafford, 2004) and White River in Indiana (Herrmann and Monaghan, 2018) also shows variability in floodplain construction and the accumulation of floodplain alluvium that further suggests a connection between Holocene fluvial dynamics and climatic variability. Although climate is accepted as a likely driver of floodplain construction, the nature and timing of floodplain construction on large Midwest streams like the Ohio River is not resolved.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies suggest that large point bar systems on the lower Ohio River rapidly evolved over the last ~2000 years (Counts et al, 2015), whereas others have concluded that they have been in a dynamic equilibrium for much of the Holocene (e.g. the Black Bottom; Alexander and Nunnally, 1972; Stafford, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This assertion may seem suspect for those familiar with geomorphic studies of meandering streams flowing through unconsolidated alluvium (Russell 1947; Leopold and Wolman 1960; Schumm 1963; Langbein and Leopold 1970; De Vorsey 1982; Garcia and Brook 1996), since a high degree of meander migration and cutoff is generally characteristic of these fluvial regimes. Even with alluvial channels, though, notable exceptions of meander stability have been observed for the Ohio River (Alexander and Nunnally 1972) and for the Missouri (Moody, Meade, and Jones 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alexander and Nunnally's [21] study of bars reconstructed from historic maps in the Ohio River's Black Bottom, Illinois, indicates the complex architecture of bars. Their study applies to both channel-side and point bars.…”
Section: Gray's River Bar Modelmentioning
confidence: 98%